Relaying protocols for buffer‐aided energy harvesting wireless cooperative networks. Issue 3 (1st May 2018) - Zhan, Jun; Liu, Yong; Tang, Xiaohu; Chen, Qingchun
Abstract : Here, the authors study a buffer‐aided relay system, in which the source node and the relay node are energy harvesting nodes, and the source node transmits the information to the destination node via the relay node. Both the source node and relay node are assumed to equipped with an energy buffer and can temporarily store the harvested energy; in addition, the relay node possesses a data buffer to store the received information temporarily. Particularly, the authors propose two buffer‐aided energy harvesting relay protocols, namely the harvest‐then‐transmit (HtT) protocol and the joint link selection and power allocation (JLSPA) protocol. For the HtT protocol, the expressions of the average achievable throughput and the optimal power splitting factor are obtained in close form. For the JLSPA protocol, based on the channel state information and buffer state information, a JLSPA protocol which maximises the average achievable throughput is presented. Furthermore, for the JLSPA protocol, the bounds on average achievable rate, average data buffer size, and average delay are analysed and the throughput‐delay trade‐off is revealed. The simulation results show that the proposed buffer‐aided relaying scheme could improve the throughput performance of energy harvesting relay system significantly.